Innovations in Partnership Based Education Financing Models - Puji Setiawan; Sigit Teguh Pujihartono; Sutrisno Sutrisno (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Education financing remains a critical issue in Indonesia due to persistent dependence on government funding, fragmented financial governance, and unequal regional financing capacity. These conditions indicate that the conventional education financing model is increasingly insufficient to address the growing complexity of educational demands. This study aims to analyze the limitations of conventional education financing and formulate a partnership-based education financing model as a more adaptive and sustainable alternative. This study employed a qualitative approach using a systematic literature review design. Data were collected from peer-reviewed journal articles, academic books, policy documents, and scientific publications published between 2020 and 2025, and were analyzed through literature reduction, categorization, thematic synthesis, interpretation, and conclusion drawing. The findings show that the conventional education financing model is constrained by excessive dependence on public budgets, bureaucratic inefficiency, weak accountability, and limited adaptability. In response, this study proposes a partnership-based education financing model designed as a collaborative financing ecosystem involving government, private sector, communities, and educational institutions. The model is structured around the principles of collaboration, sustainability, and accountability, and implemented through sequential stages of needs assessment, stakeholder mapping, partnership formulation, implementation, monitoring, and evaluation. This study concludes that partnership-based education financing offers a more flexible, diversified, and sustainable framework for strengthening educational quality and financial resilience in Indonesia.